A.6 Vagus Nerve Stimulation in patients with therapy resistant generalized epilepsy. (November 2021) - Suller Marti, AS; Mirsattari, SM; MacDougall, KW; Steven, D; Parrent, A; Andrade, A; de Ribaupierre, S; Diosy, DC; McLachlan, R; Burneo, JG
Abstract : Background: For patients with generalized epilepsy who do not respond to anti-seizure medications, the therapeutic options are limited. Vagus nerve stimulation (VNS) is a treatment mainly approved for therapy resistant focal epilepsy. There is limited information on the use of VNS on generalized epilepsies, including Lennox Gastaut Syndrome(LGS) and genetic generalized epilepsy(GGE). Methods: We identified patients with a diagnosis of Lennox-Gastaut Syndrome or Genetic Generalized Epilepsy, who underwent VNS implantation, between1997 and July 2018. Results: A total of 46 patients were included in this study with a history of therapy resistant generalized epilepsy. The mean age at implantation was 24 years(IQR= 17.8-31 years) and 50%(n=23) were female. The most common etiologies were GGE in 37%(n=17) and LGS in 63%(n=29). Median follow-up since VNS implantation was 63 months(IQR:31-112.8months). 41.7%(n=12) of the LGS group became responders, and 64.7%(n=11) in the GGE group. The best response in seizure reduction was seen in generalized tonic-clonic seizures. There was a reduction of seizure-related hospital admissions from 89.7%(N=26) pre-implantation, to 41.4%(N=12) post-implantation (p<0.0001). The frequency of side effects due to the stimulation was similar in both groups(62.1% in LGS and 61.1% in GGE). Conclusions: VNS is an effective treatment in patients with therapy resistant generalized epilepsy, especially GGE.